A TWO-YEAR FOLLOW-UP OF A FEMALE PATIENT WITH RECURRENT PULMONARY THROMBOEMBOLISM AFTER SUCCESSFUL COMBINED TREATMENT - I. A. Baranova; M. V. Zaikina; L. Yu. Sokolova; L. G. Tokareva; G. O. Ivanova; S. A. Biryukov; E. V. Filippov (Klinicist, 2015)
Objective: to describe a clinical case of recurrent pulmonary thromboembolism (PTE) with developed chronic thromboembolic pulmonary hypertension (CTEPH) and successful stenting of the pulmonary artery branch after ineffective thrombolysis. Patient Ch. born in 1978 was admitted to a cardiology unit with suspected PTE. The patient complained of obvious resting dyspnea increasing with minimal physical exercise. Blood test revealed leukocytosis, D-dimer just above the normal value. Electrocardiography showed sinus rhythm, right axis deviation, and complete right bundle-branch block. EchoCG indicated right hearth dilatation with an increase in systolic pressure gradient across the tricuspid valve up to 60 mm Hg. Lower extremity venous duplex scanning revealed a muscle vein dilated up to 14 mm with echogenic parietal deposits in the muscle thickness at the middle third of the right leg; compression was virtually complete; the valves were incompetent and a muscle vein irregularly dilated up to 7 mm in the middle third of the left leg; the walls were uneven; compression was complete. Angiopulmonography detected occlusion of the lower and middle lobe branches of the right pulmonary artery and the lower lobe branch of the left pulmonary artery. Results. It was decided to perform local thrombolysis in terms of the patient»s young age, obvious clinical symptoms (New-York Heart Association Functional Class (FC) III–IV dyspnea) and the data of earlier studies on the benefit from thrombolysis in intermediate-risk persons and a council of a vascular surgeon, a cardiologist, and an X-ray endovascular diagnosis and treatment physician, and an invasive specialist. The patient underwent local thrombolysis with purolase 6,000,000 IU. Control angiopulmonography revealed no positive changes in the branches of the pulmonary artery. Because of ineffective thrombolysis and the persistence of significant pulmonary hypertension and FC III–IV dyspnea, the patient underwent conduction recanalization of the area of left lower lobe pulmonary artery occlusion, percutaneous transluminal balloon angioplasty, and endoprosthesis replacement with an 8.0–29-mm holometallic peripheral stent. Control angiopulmonography showed that the arterial lumen was completely restored and blood flow was not distally embolized. Conclusion. This clinical case is an example of the delayed diagnosis of recurrent PTE, which was a reason for ineffective thrombolytic therapy that had been performed 11 days after the onset of an episode. In this situation, percutaneous transluminal balloon angioplasty and pulmonary artery branch stenting can improve the status of a patient and reduce the risk of CTEPH in the future. In spite of its apparent ease, angioplasty can cause problems: impossibility and hazard of enhanced contrasting of the pulmonary artery; extensive injury of its branches; arterial cicatricial process associated with multiple episodes of PTE. After angioplasty, patients may develop reperfusion pulmonary edema, the causes of which are fully unclear. However, the successful intervention makes it possible to lower pulmonary artery pressure, pulmonary vascular resistance, and blood NT-proBNP levels and to increase exercise tolerance. At the present time, a number of centers are performing such procedures in patients with CTEPH. This requires 2–3 balloon inflations per session. Holometallic stent placement can decrease the number of necessary inflations and reinterventions in the future. This clinical case demonstrates that pulmonary artery stenting is successful in the patient with recurrent PTE after ineffective thrombolysis.